The impact of parents migration on the well-being of children left behind: Initial evidence from Romania - Alina Botezat; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Many children grow up with parents working abroad. Economists are interested in the achievement and well-being of these home alone children to better understand the positive and negative aspects of migration in the sending countries. This paper examines the causal effects of parents' migration on their children left home in Romania, a country where increasingly more children are left behind in recent years. Using samples from a unique representative survey carried out in 2007 instrumental variable and bivariate probit estimates have been performed. Our initial evidence demonstrates that in Romania home alone children receive higher school grades, partly because they increase their time allocation for studying. However, they are more likely to be depressed and more often suffer from health problems especially in rural areas.
urn:nbn:de:bsz:180-madoc-367378
Keywords: I12; I21; J13; 330; parent migration; home alone children; well-being; Romania